1998
DOI: 10.1177/00220345980770100601
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-α Receptor Subunit Expression Down-regulated by IL-1β in Human Periodontal Ligament Cells

Abstract: The responses of cells to the distinct PDGF isoforms have been correlated directly to the relative numbers of specific PDGF receptor subunits on the cell surface. The modulation of PDGF-alpha receptor subunits, the major subunit expressed in human periodontal ligament (PDL) cells, by cytokines present in the periodontal wound site, such as interleukin-1 (IL-1), may be an important factor influencing regenerative outcomes. The purpose of the present study was to examine the effects of IL-1 beta on PDGF-alpha re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Volume 76 • Number 10 a v, and b 1 integrin subunits. [21][22][23] DNA sequencing of amplicons performed at the University of Texas Health Science Center at San Antonio (UTHSCSA) DNA Core Facility confirmed that the integrin subunits and aldolase corresponded with published gene sequences in GenBank. Following amplification, PCR products were separated on 2% agarose gels, which were stained with ethidium bromide and visualized using ultraviolet illumination.…”
Section: Fibroblast Integrin Expression On Implant Surfacesmentioning
confidence: 79%
“…Volume 76 • Number 10 a v, and b 1 integrin subunits. [21][22][23] DNA sequencing of amplicons performed at the University of Texas Health Science Center at San Antonio (UTHSCSA) DNA Core Facility confirmed that the integrin subunits and aldolase corresponded with published gene sequences in GenBank. Following amplification, PCR products were separated on 2% agarose gels, which were stained with ethidium bromide and visualized using ultraviolet illumination.…”
Section: Fibroblast Integrin Expression On Implant Surfacesmentioning
confidence: 79%
“…In the present only the ligand BMP‐2 was found to induce both Smurf1 and Smad6 mRNA expression in the bone cells, suggesting that surface BMPR‐IB degradation mediated by BMP‐2 up‐regulation of the Smurf1/Smad6 pathway may at least partly explain the apparent anomaly between BMPR‐IB mRNA and surface antigen expression in BMP‐2‐treated bone cells. However, it is also possible that other post‐transcriptional processes could play a part in the regulation of the BMPR‐IB surface antigen, such as rapid breakdown of mRNA transcripts and also shedding of a soluble form of the cell surface antigen, as has previously been reported for a number of other growth factor receptors (Oates et al, 1998; Philip et al, 1999; Yabkowitz et al, 1999; Hanneken, 2001; Hu et al, 2004; Sahin et al, 2004). …”
Section: Discussionmentioning
confidence: 90%
“…MiR-433 expression was found highly stimulated by IL-1β compared with PBS control-treated hL-MSC (up to 4 fold compared to PBS control, Figure 2A ), suggesting a potential function of miR-433 in response to IL-1β in hL-MSC. To assess the possible target genes that could be suppressed by miR-433 in hL-MSC, we investigated the expression of genes that are known to be inhibited by IL-1β, such as collagen type 2 (COL2A1), endothelial nitric oxide synthase (eNOS), PDGF-alpha receptor subunit (PDGF-αR), glutathione S-transferase GSTA2 and GSTM1, and sodium-taurocholate cotransporting polypeptide (NTCP) [ 28 32 ]. Consistent with prior data, these genes were all down-regulated by IL-1β (Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%